Perbandingan Kadar Senyawa Fenolat Dan Daya Antioksidan Pada Teh Celup Dengan Teh Kiloan Dari Beberapa Produk Teh Yang Beredar - Roslinda Rasyid; Dinul Aufa; Krisyanella Krisyanella (STIFARM Padang, 2011)
The determination of phenolic compounds and it’s antioxidant activity of a few tea samples of sacked tea and unsacked tea which is found at the market has been done. The Acquisition of phenolic compound content done by using Folin-Ciocalteau method and it’s antioxidant activity measurement using DPPH as an oxidant (free radical), gallat acids used as the comparison. The results showed that four samples tested unsacked tea KA has the strongest antioxidant activity among the other three samples, because It has the lowest IC50 value. The IC50 value influenced by it’s phenolic concentration. The phenolic content from unsacked tea KA obtained 39.5487 mg/g, while on samples of tea sacked KA, sacked SW, and unsacked 2K respectively: 19.754 mg/g; 33.9279 mg/g ; and 27.9814 mg/g.